Estimation of the seismic magnitude from records and hypocentral parameters for the Ñaña station - Anchivilca Valentín, Renzo Isaac (2021)
Estimating the magnitude of any seismic event is fundamental in Seismology because it allows to have an idea of earthquake size and the seismic energy released. The purpose of this research is define an empirical equation of seismic magnitude obtained through the linear regression model multiple, proposing a dependency with what is recorded in a seismic station by means of a sensor triaxial very broadband (VBB), epicentral distance and focal depth data. They were used seismic signals that are freely provided by Incorporated Research Institutions for Seismology (IRIS) based on what was recorded at the Ñaña station (NNA). The epicentral distance values were obtained from the geographical location of the recording station and the epicenters of each seismic event; while the focal depth and magnitude data were obtained from a catalog of National Earthquake Information Center (NEIC). They were obtained results of magnitude very close to those recorded by the NEIC, finding a maximum difference of 0.3 between them.